2021
DOI: 10.3390/su13063491
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable Virtual Teams: Promoting Well-Being through Affect Management Training and Openness to Experience Configurations

Abstract: A disruptive digitalization recently occurred that led to the fast adoption of virtual teams. However, membership diversity and team virtuality threaten members’ well-being, especially if faultlines appear (i.e., subgroups). Considering the job demands–resources model and the role of group affect in shaping members’ perceptions of well-being, we test the effectiveness of a short-term affect management training for increasing members’ eudaimonic well-being. Moreover, based on the trait activation theory and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 122 publications
(292 reference statements)
0
4
0
Order By: Relevance
“…On the other hand, HEIs are also organizations in which sustainability must be integrated into their strategy. Therefore, HEIs should pay attention not only to training in skills, behaviors, and values in terms of their contribution to sustainable and competitive organizations [12][13][14], but also promoting educational strategies and methodologies oriented to pursue their own sustainability as organizations [15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, HEIs are also organizations in which sustainability must be integrated into their strategy. Therefore, HEIs should pay attention not only to training in skills, behaviors, and values in terms of their contribution to sustainable and competitive organizations [12][13][14], but also promoting educational strategies and methodologies oriented to pursue their own sustainability as organizations [15].…”
Section: Introductionmentioning
confidence: 99%
“…Organizations must also address a wide range of practices and procedures that allow them to approach and deal effectively with the demands of the environment in which they operate while ensuring the safety and well-being of their members [16][17][18]. Under this background, some key issues have been highlighted by the organizations [14,17,[19][20][21][22][23] such as the promotion of innovative work behaviors, work commitment, and teamwork in a sustainable way [6]. Thus, for HEIs the challenge is even greater: they must be the driving force in the training of future professionals and members of organizations in terms of both hard and soft skills.…”
Section: Introductionmentioning
confidence: 99%
“…The research of these authors has focused primarily on social issues of VW, such as the psychological consequences for individuals, the increased social isolation, and virtual leadership during virtual communications (Bavel et al, 2020;Karl, Peluchette, & Aghakhani, 2022;Waizenegger, McKenna, Cai, & Bendz, 2020;Wiederhold, 2020). González-Anta, Orengo, Zornoza, Peñarroja, and Gamero (2021) argued that the sustainability of virtual work depends primarily on the development of employee well-being. Brunelle and Fortin (2021) found that virtual organizations play a substantial role in employees' satisfaction, where autonomy to perform tasks, competence to manage duties efficiently, and relatedness and connectedness with co-workers are valued concepts.…”
Section: Introductionmentioning
confidence: 99%
“…It is noticeable that there is a significant growth in international business, and that the increase in the number of multinationals and the multiplicity of their branches is one of the manifestations of this growth. On the other hand, the dependence of multinational companies on global virtual teams is increasing dramatically, especially with the increasing development of information and communication technology due to its great advantages (Ben Sedrine et al, 2020;Mysirlaki & Paraskeva, 2020;Han et al, 2020;Glikson & Erez, 2020;Soon & Salamzadeh, 2020;Müller & Antoni, 2020;Garro-Abarca et al, 2021;González-Anta et al, 2021;Shaik et al, 2021;Zhang et al, 2022;Lin & Roan, 2021;Mayer et al, 2020). Statistics indicate an increasing growth of remote work in the virtual work method.…”
Section: Introductionmentioning
confidence: 99%